(untitled) (Global Journal of Science Frontier Research, 2015)
The chemical composition of the extract of the stem bark of Theobroma cacao and its biological activity is hereby studied. Dried pulverised stem bark extract of Theobroma cacao was batch extracted with ethanol. This crude ethanol extract was screened for the presence of plant chemicals: the result showed the presence of alkaloid, tannin, saponin, glycoside, phenol, flavonoid and carboxylic acid. Four human pathogens; Escherichia coli, Pseudomonas aeruginosa, Streptococcus pnemoniae and Staphylococcus aureus were used in the test for the biological activity and were discovered to be susceptible to the crude extract. The extract was acidified with concentrated hydrochloric acid (HCl) and extracted with chloroform (CHCl 3 ). The organic layer was basified with 1 M sodium hydroxide (NaOH) solution and the alkaline layer treated with HCl.